Optimization of gold core-mesoporous silica shell functionalization with TPGS and PEI for cancer therapy - Rodrigues, Ana Carolina Félix (2021)
Photothermal therapy (PTT) has captured the attention of different researchers around the world, since the application of NIR light responsive-nanomaterials has shown promising results in cancer therapy. Gold-core mesoporous silica shell (Au-MSS) nanoparticles allow the combination of gold mediated PTT with the drug delivery in order to improve their therapeutic potential. In this study, two different methodologies, electrostatic or chemical linkage, were explored to functionalize Au-MSS nanorods with TPGS and PEI. For that purpose, the TPGS and PEI were chemically coupled to each other or modified with 3-(triethoxysilyl)propyl isocyanate. The produced Au-MSS nanorods display a uniform morphology and a well-defined gold nucleus and silica shell. Further, the particles surface charge was dependent on the synthesis methodology. The particles modified by electrostatic interactions (Au-MSS/TPGS-PEI) were slightly negative (−16.9 and −5.1 mV) whereas the formulations produced by chemical linkage (Au-MSS/TPGS/PEI) resulted in positively charged nanoparticles (30.9 and 6.8 mV). The successful incorporation of the polymers was confirmed by Fourier Transformed Infrared spectroscopy and thermogravimetric analysis. Moreover, the Au-MSS functionalization did not affect the particles PTT capacity. However, the Au-MSS/TPGS/PEI nanorods displayed a decreased drug encapsulation efficiency. In vitro assays demonstrated the cytocompatibility of Au-MSS up to concentrations of 200 μg/mL, however the positively charged formulations only remained biocompatible until 100 and 125 μg/mL. Overall, the attained data confirm the successful modification of Au-MSS nanorods with TPGS and PEI as well as their applicability as PTT and drug delivery agents.